Intellectual Capital and Banking Efficiency: Evidence from Banks Listed on The Indonesia Stock Exchange - Syifa, Warda Naila; Setiawan (Jurusan Akuntansi Politeknik Negeri Bandung, 2025)
This study examines the effect of intellectual capital components, namely Value Added Capital Employed (VACA), Value Added Human Capital (VAHU), and Structural Capital Value Added (STVA), on banking efficiency measured by the Operating Expenses to Operating Income (BOPO) ratio, with Return on Assets (ROA) as a moderating variable and Capital Adequacy Ratio (CAR) and firm size as control variables. The study uses panel data from banking companies listed on the Indonesia Stock Exchange during the 2012–2024 period and applies a Fixed Effects Model. The results indicate that VACA does not have a significant effect on BOPO, while VAHU and STVA have a negative and significant effect, indicating their role in improving operational efficiency. ROA moderates the relationship between VAHU and STVA on BOPO but does not moderate the effect of VACA. In addition, firm size and CAR significantly influence banking efficiency, highlighting the importance of human and structural capital management in reducing operational costs in the banking sector.